Queen Caging and Oxalic Acid Treatment: Combined Effect on Vitellogenin Content and Enzyme Activities in the First Post-Treatment Workers and Drones, Apis mellifera L - Sagona, Simona; Coppola, Francesca; Nanetti, Antonio; Cardaio, Ilaria; Tafi, Elena; Palego, Lionella; Betti, Laura; Giannaccini, Gino; Felicioli, Antonio (Animals (Basel), 2022)
Varroa destructor is a mite causing serious damage to western honey bees. Managed colonies require artificial varroa control, which may be best obtained by combining mechanical and chemical methods. This study explored the possible effects of the combination of queen caging and oxalic acid treatment on the immune system (glucose oxidase, phenoloxidase, and vitellogenin) and antioxidant enzymes (superoxide dismutase, catalase, and glutathione S transferase) of first post-treatment generation drones and workers (newly emerged, nurses, and foragers). The combination of queen caging and oxalic acid treatment caused a decrease in glucose oxidase activity only in drones. This could cause issues of cuticular sclerotization, making a drone prone to bite injuries, dehydration, and pathogens. No differences in phenoloxidase activity were recorded in both post-treatment drones and workers generation. Among worker bees, the treatment determined a lower vitellogenin content in newly emerged bees while the result was higher in nurse bees. However, the treatment did not significantly affect the antioxidant enzymes activity in either drones or workers. The results obtained in this investigation suggest that the combined anti-varroa treatments had no negative effects on oxidative stress in the first post-treatment generation bees, while effects did occur on the immune system. Further investigations on the potential effects of glucose oxidase decrease in drones and vitellogenin content variation in workers are desirable.